O torso-formních vektorových polích na Riemannových prostorech 2. řádu - Pilařová, Dagmar; Mikeš, Josef (Univerzita Pardubice, 1999)
In this article are showed fundamental relations of torso-forming vector fields on Riemannian spaces order two and a proof of a sentence delivering another results for concircular fields on Riamannian spaces order two.
Keywords: matematika; Riemannovy prostory; vektorová algebra